1982
DOI: 10.2527/jas1982.545989x
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria Acervulina Infection in Chicks Fed Excess Copper in the Presence or Absence of Excess Dietary Methionine

Abstract: Five experiments were conducted with young, male, crossbred chicks to investigate the effects of experimental Eimeria acervulina infection on the efficacy of supplemental Cu and (or) methionine when added to a corn-soybean meal diet. Duodenal coccidiosis (due to E. acervulina) and supplemental Cu (500 and 750 mg/kg) depressed weight gain and efficiency of feed utilization. Supplemental Cu increased concentrations of Cu in liver and gallbladder; experimental coccidiosis resulted in a two- to fourfold increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
5
1
Order By: Relevance
“…Our results show that the effect of A. galli infection on the copper liver level is completely different to that of coccidiosis (SOUTHERN & BAKER, 1982). This difference is probably due to the different migratory patterns of the two parasites during their developmental stages.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our results show that the effect of A. galli infection on the copper liver level is completely different to that of coccidiosis (SOUTHERN & BAKER, 1982). This difference is probably due to the different migratory patterns of the two parasites during their developmental stages.…”
Section: Discussioncontrasting
confidence: 54%
“…They concluded the sulphate and acetate forms of copper were superior to either the oxide or the carbonate ones. SOUTHERN & BAKER (1982) reported that copper absorption was dramatically increased by intestinal coccidiosis (Eimeria acervulina) in chicks. Thus an important interrelationship was demonstrated between intestinal parasitism and excess copper ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…All data were analyzed by analysis of variance, using procedures appropriate for factorial treatment designs (Steel and Torrie, 1980). Because the original kidney Cd data were heteroscedastic, one was added to all observations and the data were then transformed to natural logarithms before statistical analysis.…”
Section: Experimental Proajdurementioning
confidence: 99%
“…Previous research (Fox et al, 1971) with Cd and cysteine gave variable results when a single dose of cysteine was given to Japanese quail consuming high Cd (75 mg/kg) diets; tissue Cd levels, however, were not examined. Also, Eimeria acervulina-induced coccidiosis was found in the case of excess copper feeding to exacerbate the deposition of this element in soft tissues (Southern and Baker, 1982). Eimeria acervulina is a common protozoan parasite which attacks the duodenum of the chick and results in significant financial losses to poultry producers.…”
Section: Introdumentioning
confidence: 99%
“…Supplementation of 0.75% Met in broilers fed low crude protein diet and challenged with a mild coccidia infection increased the severity of coccidiosis, indicating the negative impact of Met supplementation on coccidiosis when birds were fed low crude protein diet ( Teng et al, 2021 ). However, there is also some research showing that the requirements of total sulfur amino acids (TSAA), Met + cysteine (Met + Cys), may be higher when chickens are infected with Eimeria species ( Southern and Baker, 1982 ; Ren et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%